Stochastic fluctuations and Brownian motion detection of gravitons - J. W. Moffat (European Physical Journal C: Particles and Fields)
Abstract We propose a way to detect gravitons by replicating the Brownian motion experiment. The number $$N_g$$ N g of gravitons can be large enough for the stochastic gravitational noise produced by them to displace a massive test particle in a physical system, allowing for the detection of gravitons. Possible experiments to detect gravitons are proposed involving collective stochastic fluctuations due to a large number of gravitons, causing a Brownian motion displacement of a massive test body. Gravitational wave experiments involving advanced interferometer techniques and mirrors could detect the large collective number of gravitons, and could detect Brownian motion of test particles in the detectors’ component mirrors. The problem of reducing thermal and other background noise is investigated.